Constantine X Doukas (1059–1067) versus Uzes – about the Nomads on Boats on the Danube in 1064 - Böhm, Marcin (Studia Ceranea, 2021)
The reign of the Doukas dynasty in 1059–1078 was a time when new threats to the Byzantine Empire emerge in Europe and Asia. One of them was the increased activity of Turkmen who were penetrating the lands belonging to the Byzantines. A manifestation of these threats was visible during the rule of Constantine X Doukas (1059–1067) in 1064. We have there an invasion of the tribe of Uzes, who crossed the Danube. They ventured so far, as the vicinity of Thessalonica and the province of Hellas, plundering everything in their path. Their actions surprised the defense of the Byzantines. This attack on the empire was related to their crossing of the Danube, about which Michael Attaliates and Skylitzes Continuatus provides us with interesting information. The main aim of this paper therefore will be related to issues linked to the types of vessels used by Uzes to cross this river, as well as an attempt to assess their boatbuilding skills.